2020
DOI: 10.1101/2020.12.30.424827
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Restoring Glutamate receptosome dynamics at synapses rescues Autism-like deficits in Shank3-deficient mice

Abstract: Shank3 monogenic mutations lead to Autism Spectrum Disorders (ASD). Shank3 is part of the glutamate receptosome that physically links ionotropic NMDA receptors to metabotropic mGlu5 receptors through interactions with scaffolding proteins PSD95-GKAP-Shank3-Homer. A main physiological function of the glutamate receptosome is to control NMDA synaptic function that is required for plasticity induction. Intact glutamate receptosome supports glutamate receptors activation and plasticity induction, while glutamate r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 55 publications
(74 reference statements)
0
7
0
Order By: Relevance
“…We next turned our attention to the activity-dependence of these interactions. We 20 , 21 and others 11 , 15 have previously reported that Homer1 dissociates from mGlu5 (and other interactors) following KCl treatment of cultured neurons or acute cortical slices stimulated in vitro. We compared peptides IP’d from WT-KCL treated mouse brain slices with those IP’d from KO-KCL-treated slices using identical methods as above.…”
Section: Resultsmentioning
confidence: 70%
See 3 more Smart Citations
“…We next turned our attention to the activity-dependence of these interactions. We 20 , 21 and others 11 , 15 have previously reported that Homer1 dissociates from mGlu5 (and other interactors) following KCl treatment of cultured neurons or acute cortical slices stimulated in vitro. We compared peptides IP’d from WT-KCL treated mouse brain slices with those IP’d from KO-KCL-treated slices using identical methods as above.…”
Section: Resultsmentioning
confidence: 70%
“…Release from the Homer scaffold can have profound effects on the activity of the Homer binding partner. By binding to the Shank–Homer scaffold, mGlu5 is spatially segregated from NMDARs, which is important for downstream signaling through ERK and mTOR pathways 15 . When mGlu5 releases from the Homer scaffold, it physically associates with NMDARs, and prevents NMDAR-mediated activation of these pathways 15 17 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many human SHANK3 mutations map to exon 21 and are associated with moderate to severe intellectual disability (D'Antoni et al, 2014;Mossa et al, 2021;Purushotham et al, 2022). Mutations in the pro-domain region of exon 21 were not associated with altered pathophysiology (Shi et al, 2017;Moutin et al, 2021). One possible explanation is that exon 21 is present in most SHANK3 isotype surrogates (Moutin et al, 2021).…”
Section: Links Between Shank3 Genes and Asdmentioning
confidence: 99%